Cuaderno de agravios y lamentaciones: múltiples voces cantan melodías tristes - Wendorff, Liliana (Mercurio Peruano, 2020)
Inspired on the moral-political philosophy of Georg Wilhelm Friedrich Hegel, this paper examines the corruption and injustice that infect Peruvian society and how the powerful block the development of the citizens in order to remain in power and acquire benefits for themselves in Cuaderno de agravios y lamentaciones by Peruvian writer Antonio Gálvez Ronceros. Each story functions as a musical note that forms part of the same melody.
Keywords: cuaderno de agravios y lamentaciones, Gálvez Ronceros, Master and Slave, peruvian society, peruvian literature